The Role of Leucine-Rich Repeat Containing Protein 10 (LRRC10) in Dilated Cardiomyopathy - Brody, Matthew J.; Lee, Youngsook (Frontiers in Physiology, 2016)
Leucine-rich repeat containing protein 10 (LRRC10) is a cardiomyocyte-specific member of the Leucine-rich repeat containing (LRRC) protein superfamily with critical roles in cardiac function and disease pathogenesis. Recent studies have identified LRRC10 mutations in human idiopathic dilated cardiomyopathy (DCM) and Lrrc10 homozygous knockout mice develop DCM, strongly linking LRRC10 to the molecular etiology of DCM. LRRC10 localizes to the dyad region in cardiomyocytes where it can interact with actin and α-actinin at the Z-disc and associate with T-tubule components. Indeed, this region is becoming increasingly recognized as a signaling center in cardiomyocytes, not only for calcium cycling, excitation-contraction coupling, and calcium-sensitive hypertrophic signaling, but also as a nodal signaling hub where the myocyte can sense and respond to mechanical stress. Disruption of a wide range of critical structural and signaling molecules in cardiomyocytes confers susceptibility to cardiomyopathies in addition to the more classically studied mutations in sarcomeric proteins. However, the molecular mechanisms underlying DCM remain unclear. Here, we review what is known about the cardiomyocyte functions of LRRC10, lessons learned about LRRC10 and DCM from the Lrrc10 knockout mouse model, and discuss ongoing efforts to elucidate molecular mechanisms whereby mutation or absence of LRRC10 mediates cardiac disease.